Day program for young people with anorexia nervosa. (June 2015) - Green, Jessica; Melvin, Glenn A; Newman, Louise; Jones, Meaghan; Taffe, John; Gordon, Michael
Objectives: This study examined changes in body mass index (BMI), anorectic cognitions, and psychological distress following day program treatment. Methods: Participants were 42 female patients from the Monash Health Butterfly eating disorder day program, with anorexia nervosa (AN) restricting type ( n = 35) or AN binge-eating/purging type ( n = 7), ranging from 12 to 24 years. Results: Participants' BMI increased significantly over time. Higher motivation at intake predicted a greater increase in BMI over time, compared to those with lower motivation at intake. There were also significant reductions in drive for thinness, body dissatisfaction, anxiety, and depression scores, and improved motivation following two, four and six months of treatment. Conclusions: These findings provide further evidence that day programs can assist in weight restoration and improvements in psychological aspects of AN in adolescents and young adults.